Comparitive Analysis of Statistics of the Direct Foreign Investment in Lithuania, Latvija, Estonia, and the Czech Republic - Vasiliauskas, Aleksandras (Ekonomika, 1997)
The purpose of this paper is to investigate the principal (methodological) differences in the statistics of foreign direct investment in Lithuania, Latvia, Estonia, and the Czech Republic and to clear up the conditions, under which it is possible to compare the official statistical data of different countries. The detailed initial definition of foreign direct investment, recommended by the Organisation for Economic Cooperation and Development (OECD) has been chosen as the standard for the comparisons. The statistics of foreign direct investment are most compatible with these recomendations only in Estonia. Foreign direct investment in the statistics of Lithuania, Latvia, and the Czech Republic are interpreted as an investment in the authorized capital of enterprise. Therefore the indicators of foreign direct investment of these countries may only be compared with one component of the total indicators in Estonia. This component, corresponding to the investment in the authorised capital of enterprise, is indicated in the statistics of the foreign direct investment of Estonia as a seperate figure.